2012
DOI: 10.5539/ijc.v4n4p62
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining Some Polymer Composites Filled with Rice Husks Ash-A Review

Abstract: Rice husks are an important by-product of rice milling process and are major waste product of the agricultural industry. Rice husk contain nearly 20 mass% silica, which is present in hydrated amorphous form. They have now become a great source as a raw biomass material for manufacturing of value-added silicon composite products, including silicon carbide, silicon nitride, silicon tetrachloride, magnesium silicide, pure silicon, zeolite, fillers of rubber and plastic composites, cement, adsorbent and support of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 123 publications
(119 reference statements)
1
26
0
Order By: Relevance
“…After simulation, the pseudo‐first‐order kinetic model showed great correlations (R 2 = 0.9254) in description of relation between ln(k/T) and 1/T , and the results were shown in Figure (b). ΔH was 40.44 kJ·mol ‐1 , implying endothermic nature of the reaction, ΔS was calculated to be ‐140.84 J mol ‐1 K ‐1 , the change of entropy could reflect the proximity of the system to its own thermodynamic equilibrium, and the value of ΔS could reflect the degree of arrangement and complexity of the products compared to the initial reagents, negative values of entropy illustrated enthalpy driven of the reaction, it can be suggested that the complex products formed in the reductive dechlorination of CT were more structured than the initial molecules and more order might be generated after the reaction …”
Section: Resultsmentioning
confidence: 99%
“…After simulation, the pseudo‐first‐order kinetic model showed great correlations (R 2 = 0.9254) in description of relation between ln(k/T) and 1/T , and the results were shown in Figure (b). ΔH was 40.44 kJ·mol ‐1 , implying endothermic nature of the reaction, ΔS was calculated to be ‐140.84 J mol ‐1 K ‐1 , the change of entropy could reflect the proximity of the system to its own thermodynamic equilibrium, and the value of ΔS could reflect the degree of arrangement and complexity of the products compared to the initial reagents, negative values of entropy illustrated enthalpy driven of the reaction, it can be suggested that the complex products formed in the reductive dechlorination of CT were more structured than the initial molecules and more order might be generated after the reaction …”
Section: Resultsmentioning
confidence: 99%
“…RHA is mainly composed by SiO 2 -about 95% -and other trace elements like potassium, calcium, magnesium, iron, copper, manganese and zinc (Della et al 2002). This composition of RHA makes it a candidate in industrial applications, with the advantage of its low cost (Turmanova et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the amount of silica present, the ash is classified as either white RHA (WRHA), which is relatively high in silica content, or black RHA (BRHA), which is relatively low in silica content. The detailed characterization of RHA has been previously reported .…”
Section: Introductionmentioning
confidence: 99%